Potential of Modified Orange Peels as Natural Coagulant for Water Turbidity Removal - Nelson, Tracy Sambai; Abdul Hamid, Nor Hazren (Progress in Engineering Application and Technology, 2024)
This research aimed to determine the suitability of aluminium sulfate (alum) and orange peels to act as a chemical coagulants and natural coagulant for water turbidity removal. The performance of these two coagulants was assessed in terms of turbidity removal using jar test experiments for synthetic low, moderate and high turbid water. The results indicated that the optimum dosage and low turbidity removal for aluminium sulfate (alum) and orange peels was found at 54 mg/l with 65.20% turbidity removal and 54 mg/l with 81.83% turbidity removal, respectively. Orange peels showed higher removal efficiency as compared to aluminium sulfate. The study demonstrated that orange peels waste has the potential to be used as a substitute for chemical based coagulant for a future alternative in water treatment. The results indicated that the optimum dosage and moderate turbidity removal for aluminium sulfate (alum) and orange peels was found at 54 mg/l with 55% turbidity removal and 54 mg/l with 71.04% turbidity removal, respectively. Orange peels showed higher removal efficiency as compared to aluminium sulfate. The study demonstrated that orange peels waste has the potential to be used as a substitute for chemical based coagulant for a future alternative in water treatment. The results indicated that the optimum dosage and high turbidity removal for aluminium sulfate (alum) and orange peels was found at 54 mg/l with 64.73% turbidity removal and 54 mg/l with 75.47% turbidity removal, respectively. Orange peels showed higher removal efficiency as compared to aluminium sulfate. The study demonstrated that orange peels waste has the potential to be used as a substitute for chemical based coagulant for a future alternative in water treatment.